Device‐related infection associated with increased mortality risk in de novo transvenous implantable cardioverter‐defibrillator medicare patients. (31st January 2022) - El‐Chami, Mikhael F.; Liu, Yiyan; Griffiths, Robert I.; Knight, Bradley P.; Weiss, Raul; Mark, George E.; Biffi, Mauro; Probst, Vincent; Lambiase, Pier D.; Miller, Marc A.; Jacobsen, Caroline M.; Baddour, Larry M.
Abstract: Introduction: Transvenous implantable cardioverter‐defibrillators (TV‐ICD) infection is a serious complication that frequently requires complete device removal for attempted cure, which can be associated with patient morbidity and mortality. The objective of this study is to assess mortality risk associated with TV‐ICD infection in a large Medicare population with de novo TV‐ICD implants. Methods: A survival analysis was conducted using 100% fee‐for‐service Medicare facility‐level claims data to identify patients who underwent de novo TV‐ICD implantation between 7/2016 and 1/2018. TV‐ICD infection within 2 years of implantation was identified using International Classification of Disease, 10th Edition and current procedural terminology codes. Baseline patient risk factors associated with mortality were identified using the Charlson Comorbidity Index categories. Infection was treated as a time‐dependent variable in a multivariate Cox proportional hazards model to account for immortal time bias. Results: Among 26, 742 Medicare patients with de novo TV‐ICD, 518 (1.9%) had a device‐related infection. The overall number of decedents was 4721 (17.7%) over 2 years, with 4555 (17%) in the noninfection group and 166 (32%) in the infection group. After adjusting for baseline patient demographic characteristics and various comorbidities, the presence of TV‐ICD infection was associated with an increase of 2.4 (95% CI: 2.08–2.85) times in the mortality hazard ratio. Conclusion: The rate of TV‐ICD infection and associated mortality in a large, real‐world Medicare population is noteworthy. The positive association between device‐related infection and risk of mortality further highlights the need to reduce infections